CRITICAL STUDY OF THE HADITH “ṢŪMŪ TAṢIḤḤŪ” AND ITS RELATION TO MEDICINE - Dewi Nurul Izzah (Nabawi: Journal of Hadith Studies, 2024)
Fasting in Islam is not only viewed as a spiritual practice but also as an activity that offers health benefits. Many individuals report improvements in their health after observing fasting; however, these claims are often based on personal experiences and religious beliefs. Therefore, more in-depth scientific studies are needed. This article examines the criticisms of the hadith "Ṣūmū Taṣiḥḥū" and its relationship with modern medical perspectives. The criticisms of this hadith arise not only from the sanad (chain of narration) and matan (text) but also from a medical standpoint, using holistic content and descriptive analysis. The research findings indicate that sanad criticism suggests this hadith is weak, while matan analysis shows that it does not contradict the Qur'an, other hadiths, or medical science. Thus, the text of this hadith is considered valid. Consequently, the hadith can be practiced according to its content without exaggeration.[Puasa dalam Islam tidak hanya dipandang sebagai ibadah spiritual, tetapi juga praktik yang membawa manfaat kesehatan. Banyak orang melaporkan peningkatan kesehatan setelah menjalani puasa, namun klaim-klaim ini sering kali didasarkan pada pengalaman pribadi dan keyakinan religius. Oleh karena itu, diperlukan kajian ilmiah yang lebih mendalam. Artikel ini mengkaji kritik terhadap hadis "Ṣūmū Taṣiḥḥū" dan hubungannya dengan perspektif medis modern. Kritik hadis ini tidak hanya dari segi sanad (rantai periwayatan) dan matan (teks), tetapi juga dari sudut pandang medis dengan menggunakan analisis konten dan deskriptif secara holistik. Hasil penelitian menunjukkan bahwa kajian kritik sanad mengatakan bahwa hadis ini lemah, sedangkan kajian matannya menunjukkan hadis ini tidak bertentangan dengan Al-Quran, hadis lain, dan ilmu medis. Maka hadis ini sahih matannya. Sehingga hadis ini dapat diamalkan secara kandungan isinya dengan porsinya yang sedemikian tanpa melebih-lebihkan.]